(untitled) - Richard A MacMahon (Cincinnati, Ohio, 2000)
The book begins with an introduction to networking terms and technology, then proceeds through network installation and access. From there, the book presents about network structure and use. Next, information on careers in the networking industry is presented.
Keywords: netware ( computer programs )